Survei indeks massa tubuh, presentase lemak dan tingkat daya tahan kardiovaskuler (VO2max) peserta Sanggar Tari Tradisi Tantya Widyawara Tunggulwulung Kota Malang - Mukharam, Khamdan; Wicaksono, Emmanuel Lukas (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2025)
Body mass index is commonly used to determine an individual's weight category. However, combining body mass index with body fat percentage provides a more accurate picture of adiposity. Body mass index also influences cardiovascular endurance (VO2Max). One method to improve cardiovascular endurance is through dancing using various choreographies and predetermined tempos. Dancing is the expression of the human soul translated into symbolic movements based on the creator's imagination. This research aims to analyze the body mass index, body fat percentage, and cardiovascular endurance level (VO2Max) of members of the Tradisi Tantya Widyawara Tunggulwulung dance troupe in Malang City. The method used in this research is quantitative descriptive with a survey and cross-sectional approach. The research subjects consist of 11 active members of the dance troupe. The results of the research show that the participants' body mass index falls within the ideal weight category, body fat percentage is normal, and cardiovascular endurance level (VO2Max) is classified as excellent.